Opportunities for management of macrophage phenotype reprogramming - V. N. Sakharov; P. F. Litvitsky (Сеченовский вестник, 2022)
This article reviews the recent literature on opportunities for reprogramming of macrophage phenotypes. Much attention is devoted to the stimulus, signal pathways and its effects as well as some regulational mechanisms.